Montessori Education and a Neighborhood School - Mary D Burbank; Melissa M. Goldsmith; Jennifer Spikner; Koeun Park (University of Kansas, 2020)
Project SYNC (Systems, Yoked through Nuanced Collaboration) details perspectives of a community of stakeholders committed to the enhancement of early childhood (i.e., prekindergarten through grade 3) education. Although there is a growing number of public-school programs informed by the Montessori philosophy, Montessori educational experiences often take place within affluent communities. SYNC aimed to enhance the prekindergarten through grade 3 educational experiences for traditionally underserved students by transforming two traditional early childhood classrooms to Montessori settings within a diverse, Title I school. Montessori pedagogy, curricula, and materials aligned with the school's dedicated commitment to social justice. The study, one in a series, explored the impact of Montessori education on a neighborhood school community as evidenced through stakeholder opinions, project implementation, and teacher attitudes. Project data illustrate that a Montessori educational experience created learning opportunities that supported children from culturally and ethnically diverse communities in a traditional, Title I elementary school.